2003
DOI: 10.1029/2002jc001369
|View full text |Cite
|
Sign up to set email alerts
|

Profiles of dimethylsulphoniopropionate (DMSP), algal pigments, nutrients, and salinity in the fast ice of Prydz Bay, Antarctica

Abstract: [1] Total dimethylsulphoniopropionate (DMSPt), chlorophyll a (Chl a), and algal marker pigments were measured in 12 fast ice cores collected from Prydz Bay, eastern Antarctica (68°-69°S, 77°-79°E) in October 1997 and November 1998. Patterns of DMSPt distribution through the ice were similar on spatial scales of meters to tens of kilometers within ice sheets grouped according to growth history. This reflects the association of DMSP in fast ice with autotrophic biomass distribution, which is intrinsically linked… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
51
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(53 citation statements)
references
References 37 publications
2
51
0
Order By: Relevance
“…4 Sea ice has been considered as a potential important source of DMS in the polar oceans when extremely high concentrations (up to three orders of magnitude higher than background sub-nanomolar seawater concentrations) of its precursor DMSP were found in Antarctic [Kirst et al, 1991] and Arctic [Levasseur et al, 1994] sea ice cores. The production of DMSP in sea ice is favored by the high concentration of its producers (i.e., ice microalgae) [Trevena et al, 2003;Gambaro et al, 2004] and by the extreme environmental conditions of the sea ice habitat. The high salt concentrations and low temperatures that prevail in sea ice favour high intracellular contents in DMSP [Kirst et al, 1991;DiTullio et al, 1998] which is known to act as a cryoprotectant and osmoregulator [Stefels, 2000;Stefels et al, 2007].…”
Section: Inorganic Carbon Dynamicsmentioning
confidence: 99%
“…4 Sea ice has been considered as a potential important source of DMS in the polar oceans when extremely high concentrations (up to three orders of magnitude higher than background sub-nanomolar seawater concentrations) of its precursor DMSP were found in Antarctic [Kirst et al, 1991] and Arctic [Levasseur et al, 1994] sea ice cores. The production of DMSP in sea ice is favored by the high concentration of its producers (i.e., ice microalgae) [Trevena et al, 2003;Gambaro et al, 2004] and by the extreme environmental conditions of the sea ice habitat. The high salt concentrations and low temperatures that prevail in sea ice favour high intracellular contents in DMSP [Kirst et al, 1991;DiTullio et al, 1998] which is known to act as a cryoprotectant and osmoregulator [Stefels, 2000;Stefels et al, 2007].…”
Section: Inorganic Carbon Dynamicsmentioning
confidence: 99%
“…DMSP release by the cell occurs during algal growth but significantly increases during cell senescence or as a consequence of zooplankton grazing, bacterial activity, and viral lysis. During sea-ice melting, DMSP and DMS released from the ice can accumulate in surface waters and lead to the occurrence of DMS concentration pulses and hot-spots (Kirst et al 1991;Levasseur et al 1994;Trevena and Jones 2006). Zemmelink et al (2005) reported that the stratification due to sea-ice melting fosters the production of DMSP and DMS in sea ice in such amounts that the resulting emission could contribute significantly to the yearly DMS flux from the Southern Ocean to the atmosphere.…”
mentioning
confidence: 99%
“…Antarctic sea ice has been shown to contain large amounts of dimethylsulphoniopropionate (DMSP) (Turner et al 1995;Trevena et al 2003;Gambaro et al 2004), which is a precursor of dimethylsulfide (DMS), another climatically active gas. Marine DMS emissions are involved in climate regulation because atmospheric oxidation products of DMS act as condensation nuclei and therefore directly (as aerosols) and indirectly affect the radiative properties of the atmosphere.…”
mentioning
confidence: 99%
“…When on-field analysis of the compounds is impossible, additional preservation techniques can be applied to preserve either the DMS or DMSP, such as the acidification technique (Curran et al 1998; Curran and Jones 2000). Trevena et al (2003) used this technique but concluded their study by mentioning some limitations of the method for the determination of DMS-related compounds. They observed that nearly all DMSP was found in the dissolved fraction and suggested that this DMSP could have partly originated from damage to the cell caused by salinity stress undergone during thawing.…”
mentioning
confidence: 99%